The Comparative of Media Framing in 2019 Presidential Election Campaign - SAKTI, Tri Nugraha; LILIWERI, Alo; RONDA, Mirza (International Journal of Environmental, Sustainability, and Social Science, 2023)
As is common knowledge, the euphoria of the election from one period to the next is a breath of fresh air for the mass media crews to favor each other when reporting on events surrounding the campaign, including the presidential election. The fact information is worth selling, and a news report that is eagerly anticipated by the public because it is a way of addressing the demand for information on the requirements of the people on specific people or groups of people who become newsworthy. National newspapers have a significant role in establishing the reality of the campaign coverage of each Presidential Candidate (Capres). The objective of this research is to examine how Republika and Media Indonesia newspapers framing their coverage of the 2019 Presidential Election Campaign between Joko Widodo and Prabowo Subianto through news articles published from 15 March to 31 March 2019. The method utilized in this study is qualitative approve a constructivist paradigm. The utilized theory is framing with the Zhong Dang and Pan Kosicki model. The results demonstrated that there were ideological differences between Republika and Media Indonesia, despite the fact that the ideology, editorial content, and ownership of the Republika newspaper did not change during the 2019 presidential election campaign, when Mr. Eric Tohir was named campaign chairman for the presidential clone Joko Widodo. There appears to have been a shift in the delivery and framing of Joko Widodo’s campaign coverage since 2014. And secondly, the prestige of political leaders.